2011
DOI: 10.2147/opth.s15028
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life in patients with end-stage age-related macular degeneration: focus on miniature ocular implants

Abstract: Video abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 22 publications
1
48
0
3
Order By: Relevance
“…The lower magnification of the IOL VIP system, on the other hand, does not result in a significant loss of visual field, while also enabling it to be better tolerated by patients when implanted in both eyes. 10,16 All of our cases tolerated this system quite well, with none of the cases requiring explantation. Two of our cases reported subjective satisfaction with the binocular implantation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The lower magnification of the IOL VIP system, on the other hand, does not result in a significant loss of visual field, while also enabling it to be better tolerated by patients when implanted in both eyes. 10,16 All of our cases tolerated this system quite well, with none of the cases requiring explantation. Two of our cases reported subjective satisfaction with the binocular implantation.…”
Section: Discussionmentioning
confidence: 65%
“…Singer et al, in their review article on the evaluation of the intraocular telescopic implants also concluded that these implants help to increase the quality of life in low vision patients. 10 Kaşkaloğlu et al published an article in 2001 summarizing their experiences with IMT intraocular telescopes with three cases. 15 In one of these cases, an iritis that developed after surgery was resolved with topical medication, while explantation was required in another case due to bubbles forming inside the telescope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An article that compares between medical results of the intraocular implant was also written (Singer, Amir, & Herro, 2012). This implant, increases the central image and suddenly decreases the peripheral vision that causes a strange vision.…”
Section: Introductionmentioning
confidence: 99%